System for control over the detoxication process and the state of an organism for patients with surgical infection - S. V. Kemerov; D. A. Styopin; A. P. Koshel; T. G. Zherlova; V. Ye. Shipakov (Бюллетень сибирской медицины, 2009)
The complexity of measures on detoxication of an organism is caused by the critical state of a patient against the background of multiple organ failure, disordered hemodynamics, pronounced changes of hemostasis, protein-energy deficiency, waterelectrolytic and acid-base disbalance. A new method is proposed for the treatment and control of the detoxication process. The positive effect of this method is caused by the syndrome-by-syndrome character of the therapy and the multilevel direction of the action. The proposed method involves all the interested organs and systems of an organism into the detoxication process.